1999
DOI: 10.1164/ajrccm.160.6.9902117
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Trial Comparing Bilateral Lung Volume Reduction Surgery to Pulmonary Rehabilitation in Severe Chronic Obstructive Pulmonary Disease

Abstract: Several uncontrolled studies report improvement in lung function, gas exchange, and exercise capacity after bilateral lung volume reduction surgery (LVRS). We recruited 200 patients with severe chronic obstructive pulmonary disease (COPD) for a prospective randomized trial of pulmonary rehabilitation versus bilateral LVRS with stapling resection of 20 to 40% of each lung. Pulmonary function tests, gas exchange, 6-min walk distance, and symptom-limited maximal exercise testing were done in all patients at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
101
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(109 citation statements)
references
References 35 publications
5
101
1
2
Order By: Relevance
“…LVRS resulted in an approximately 20% reduction in the percentage of patients exhibiting ventilatory limitation as a primary cause for exercise termination. These data support improvements in lung, 14,15,18,26,27 chest wall, 9,16 and respiratory muscle mechanics, 5,7 as responsible for enhancing exercise performance following LVRS. Our data show that ventilatory improvements occur following LVRS throughout the continuum of exercise, from submaximal (unloaded cycling) through maximum symptom-limited exercise workloads.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…LVRS resulted in an approximately 20% reduction in the percentage of patients exhibiting ventilatory limitation as a primary cause for exercise termination. These data support improvements in lung, 14,15,18,26,27 chest wall, 9,16 and respiratory muscle mechanics, 5,7 as responsible for enhancing exercise performance following LVRS. Our data show that ventilatory improvements occur following LVRS throughout the continuum of exercise, from submaximal (unloaded cycling) through maximum symptom-limited exercise workloads.…”
Section: Discussionsupporting
confidence: 63%
“…[3][4][5][6][7][8][9] Dynamic hyperinflation and an elevated work of breathing precipitate breathlessness, thereby decreasing exercise tolerance and quality of life. 1,10,11 Lung volume reduction surgery (LVRS) increases lung elastic recoil 12 and decreases end-expiratory lung volume, 3,6,13,14 thereby improving lung [15][16][17][18] and respiratory muscle mechanics 5,7 and overall exercise tolerOriginal Research CARDIOTHORACIC SURGERY ance. 19 -24 However, most of the published reports are uncontrolled, unicenter trials involving small numbers of patients with short-term follow-up.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lung volume reduction surgery (LVRS) has been shown to have a beneficial effect on lung function, submaximal exercise capacity and quality of life in selected patients with severe emphysema [1][2][3], although individual results classically demonstrate large scatter [1]. Initially, it was proposed that the increase in maximal expiratory flow (MEF) observed after LVRS was mainly due to an improvement in lung elastic recoil after the surgical procedure [4].…”
mentioning
confidence: 99%
“…Several large case series from centres with considerable experience have demonstrated a low operative mortality (v5%) and significant improvements in symptoms, pulmonary function, and exercise capacity in the short and intermediate term after LVRS [3][4][5][6][7]. Three prospective randomised studies confirmed functional improvements in the operated group, whereas this was not observed in the conservativelytreated control arm [8][9][10]. Nonetheless, controversy remained with respect to potential benefits and risk of the procedure [11,12].…”
mentioning
confidence: 99%